使用任务教学法进行汉语教学的影响 ——以“KOPERASI高中一年级的学生”为例—— - Annisa Septiningsih; Ina Ina; Tjen Veronica (Universitas Tanjungpura, 2022)
AbstractAt this time, Mandarin has been widely studied in schools. There are several competencies in learning Mandarin that students must master, such as good pronunciation, writing, and memorizing a lot of vocabularies. However, according to the majority of students, Mandarin is very difficult to learn. Improving students ability in learning Mandarin, the writer use a task based approach to students in class X SMA Koperasi Pontianak. The purpose of this study was to find out the improvement of the student’s ability in the class X of SMA Koperasi Pontianak by implementing the task based approach method in learning Mandarin. The research methodology used in this research was classroom action research and tests. Classroom action research started on January 20th, 2021 until February 17th, 2021. The test method in this study was divided into pre-test and post-test. Based on the results, the pre-test showed that the average score of the class was 61.29 for Mandarin subject. Meanwhile, based on the post-test results, it showed that the average score was 85.44. This proves that the task based approach method can improves students’ ability in learning Mandarin and improve students’ ability to learn independently.Keywords: Mandarin, Task Based Approach, Teaching Method